2021
DOI: 10.3390/ijerph18105167
|View full text |Cite
|
Sign up to set email alerts
|

Parental Nonstandard Work Schedules and Child Development: Evidence from Dual-Earner Families in Hong Kong

Abstract: With the emergence of 24/7 economies, the practice of working nonstandard schedules has become increasingly common. This trend raises a concern about how parental nonstandard work schedules affect child development outcomes. Using data from dual-earner families with young children (age 5–6) in Hong Kong, this study examined the association between parental work schedules and child development. It also examined under what conditions parental nonstandard work schedules affect child development, with a focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Guided by cognitive-behavioral and social learning principles, Workplace Triple P has been shown to be effective in reducing work-family conflicts and enhancing parenting efficacy among working parents ( Hartung and Hahlweg, 2011 ; Haslam et al, 2013 ). Though it has yet to be used in the local context, the demonstrated effectiveness of the original Triple P for Hong Kong parents ( Leung et al, 2003 , 2014 ) suggests that Workplace Triple P is also likely to benefit working parents in Hong Kong ( Kim, 2021 ), where practitioners are ready to offer the evidence-based parenting program ( Kim, 2019a , 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Guided by cognitive-behavioral and social learning principles, Workplace Triple P has been shown to be effective in reducing work-family conflicts and enhancing parenting efficacy among working parents ( Hartung and Hahlweg, 2011 ; Haslam et al, 2013 ). Though it has yet to be used in the local context, the demonstrated effectiveness of the original Triple P for Hong Kong parents ( Leung et al, 2003 , 2014 ) suggests that Workplace Triple P is also likely to benefit working parents in Hong Kong ( Kim, 2021 ), where practitioners are ready to offer the evidence-based parenting program ( Kim, 2019a , 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing that parental experiences at the workplace may spill over to the family, a growing body of research has examined the association between parental work schedules and child wellbeing ( Kaiser et al, 2017 ; Kachi et al, 2021 ). In the Chinese context, for instance, recent studies by Han (2020) and Kim (2021) showed that parental non-standard work schedules were associated with various developmental outcomes for young children in Hong Kong and mainland China, respectively. Previous research, however, has tended to focus on the direct linkage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Hong Kong particularly, Kim (2021) studied the relationships between nonstandard work schedules (NWSs) and child development. The study revealed that Paternal NWSs were found to be negatively related to total child development.…”
Section: Dual Earner Income Parentsmentioning
confidence: 99%